Kebijakan Pemerintah Menangkal Penyebaran Berita Palsu atau ‘Hoax’ - Kurniawan Hari Siswoko (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2017)
The massive and rapid spreading of fake news through the internet and social media has prompted the government to take steps to contain the hoaxes. Initially, the government was confident that the spread of fake news could be countered by blocking a number of irresponsible newsite. This research argues that the blocking of the newsite will not be effective in countering fake news. Thus, the government would need additional measures to deal with the massive and rapid spread of fake news through the internet. This research is conducted through observation and content analysis of media reports about the government policies regarding the spread of fake news. According to Berelson (1952) content analysis is a research technique for the objective, systematic, and quantitative description of the manifest content of communication. Holsti (1968) says that it is any technique for making inferences by systematically and objectively identifying specified characteristics of messages. This research found several other measures the government has taken that includes the establishment of a special agency to deal with the cyberspace and collaborations with the Press Council and Facebook to strengthen its efforts. Keywords:  fake news, government policies, national cyber agency, hoax